Rare-earth permanent magnet in magnetic system of electron accelerator with the energy of 10 MеV - Bovda, V.A.; Bovda, A.M.; Guk, I.S.; Kandybey, S.S.; Kononenko, S.G.; Lyashchenko, V.N.; Mytsykov, A.O.; Onischenko, L.V. (Вопросы атомной науки и техники, 2019)
The radiation resistance of Sm-Co and Nd-Fe-B magnets under 10 MeV electron beam was studied. The simulation and design of a magnetic system for electron beam analysis of a technological accelerator for energy up to 10 MeV was carried out. The key component of magnetic system was Sm₂Co₁₇ magnets with the size of 30х24х12 mm. The maximum magnetic field in the magnetic system was 0.3 T. Експериментально досліджена радіаційна стійкість магнітних матеріалів зi Sm-Co- і Nd-Fe-B-сплавів під дією 10 МэВ електронного пучка. На основі зразків зi Sm₂Co₁₇-сплаву розмірами 30х24х12 мм проведені моделювання і конструювання магніту для аналізу пучка електронів технологічного прискорювача на енергію 10 МеВ. Приведено результати експериментального дослідження характеристик магніту. Максимальне поле в магніті дорівнює 0,3 Тл. Экспериментально исследована радиационная стойкость магнитных материалов из Sm-Co- и Nd-Fe-B-сплавов под действием 10 МэВ электронного пучка. На основе образцов из Sm₂Co₁₇-сплава размерами 30х24х12 мм проведено моделирование и конструирование магнита для анализа пучка электронов технологического ускорителя на энергию 10 МэВ. Приведены результаты экспериментального исследования характеристик магнита. Максимальное поле в магните равно 0,3 Тл.